2008
DOI: 10.1088/0953-4075/41/13/135203
|View full text |Cite
|
Sign up to set email alerts
|

Projectile interactions in theoretical triple differential cross sections for simultaneous excitation–ionization of helium

Abstract: The importance of projectile interactions in triple differential cross sections (TDCS) is explored for the problem of simultaneous excitation–ionization of helium by electron impact using a new approach that we call the four-body distorted wave model (4DW). The 4DW model includes all projectile interactions, namely initial- and final-state projectile–target interactions, and the post-collision interaction between the two continuum electrons. Results are presented for an incident electron energy of 500 eV and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 25 publications
3
25
1
Order By: Relevance
“…[9], and we present only the relevant details here. For an * harrisal@hsu.edu electron incident on a target with two active electrons, there are three indistinguishable electrons involved in the collision.…”
Section: Theorymentioning
confidence: 99%
See 3 more Smart Citations
“…[9], and we present only the relevant details here. For an * harrisal@hsu.edu electron incident on a target with two active electrons, there are three indistinguishable electrons involved in the collision.…”
Section: Theorymentioning
confidence: 99%
“…In our previously published First Born Approximation (FBA) and 4DWD results [6,9,10], the exchange and capture amplitudes were neglected, and only the direct amplitude was calculated. This effectively labeled the electrons and ignored any indistinguishability.…”
Section: Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…They have compared their relative experimental data with two different theoretical models, namely, momentum space close-coupling (CCC) and configuration space R-matrix with pseudostates (RMPS) and found the importance of accounting for secondorder effects in the projectile-target interaction. Very recently, Harris et al [4] reported a new model, the four-body distorted wave (4DW) model to study the electron impact excitationionization process of helium. The 4DW model considers all projectile interactions including the initial-and final-state projectile-target interactions and the post-collision interaction between the two continuum electrons.…”
Section: Introductionmentioning
confidence: 99%